Research on Privacy-by-Design Behavioural Decision-Making of Information Engineers Considering Perceived Work Risk - Fei Bu; Nengmin Wang; Qi Jiang; Xiang Tian (Systems, 2024)
Privacy by design (PbD) has attracted considerable attention from researchers and information security experts due to its enormous potential for protecting private information and improving the privacy and security quality of information technology products. The adoption of PbD among information engineers is currently limited owing to its innovativeness and the distinctive traits of the information technology industry. Utilising the Technology Acceptance Model as a framework, this study innovatively explores the pivotal factors and mechanisms that influence information engineers’ decision-making in the adoption of PbD from the viewpoint of the perceived work risk. In this empirical research, professional information engineers were invited to complete a questionnaire survey. After analysing the data using partial least squares structural equation modelling, the results reveal that information engineers’ perceived work risk in PbD (PWRP) negatively affects their perceptions of the usefulness and ease of use of PbD. This negative perception subsequently reduces their intention to implement PbD (INTP) and adversely impacts their attitudes towards implementing PbD (ATTP). Furthermore, the study findings reveal that a positive ATTP among engineers boosts their INTP and positively influences their behaviours regarding information security. This study provides an in-depth examination of these findings and lays a solid theoretical groundwork for the further promotion and implementation of PbD in information technology enterprises. Moreover, the findings offer invaluable support for management decisions in both information technology companies and information security regulatory authorities, significantly contributing to the expansion and deepening of research in the field of PbD.